2016
DOI: 10.5152/balkanmedj.2016.140172
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sodium Hyaluronate plus Sodium Chondroitin Sulfate Solution on Peritendinous Adhesion and Tendon Healing: An Experimental Study

Abstract: Background: Adhesion formation following tendon injury is a serious clinical problem. Aims: In this experimental study, the effects of the combination of sodium hyaluronate (HA) and chondroitin sulfate (CS) on peritendinous adhesion and tendon healing were evaluated. Study Design: Animal experimentation. Methods: Twenty-one mature Sprague Dawley male rats were randomly divided into three equal groups. The rats' Achilles tendons were cut and repaired with a modified Kessler technique. About 0.25 and 0.50 mL of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…However, the performance of selective COX-2 inhibitors used in clinic remains unclear. Several experimental studies of NSAID treatment on rats have revealed NSAID could impair healing of supraspinatus reattachment, patellar tendon reattachment, and the Achilles tendon [ 30 33 ]. To our knowledge, our study is the first time to investigate whether celecoxib could affect functional healing in patients undergoing ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the performance of selective COX-2 inhibitors used in clinic remains unclear. Several experimental studies of NSAID treatment on rats have revealed NSAID could impair healing of supraspinatus reattachment, patellar tendon reattachment, and the Achilles tendon [ 30 33 ]. To our knowledge, our study is the first time to investigate whether celecoxib could affect functional healing in patients undergoing ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al [13] investigated the feasibility of using adipose derived stem cells (ASCs) for engineered tendon repair in vivo in a rabbit Achilles tendon model, and they found no difference in tensile strength at 5 weeks but found significant difference at the time points of 12 weeks, 21 weeks, and 45 weeks. Some other studies also show treatment of HA strongly improved the biomechanical properties of the injured tendons and the ultimate strength [10, 27]. One conceivable possibility is that, unlike with the normal Achilles tendon, PET artificial ligament has much better characteristic of strength and stiffness, and injection of HA may not add significant improvement of biomechanical property to PET artificial ligament.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial ligaments can promise a fast functional recovery and avoid complications. In addition, there are various treatments applied for helping the healing of tendon injuries such as platelet-rich plasma (PRP) [8, 9] and sodium hyaluronate (HA) [10]. Sodium hyaluronate (HA) is polysaccharide, which is found in all extracellular matrix of vertebrates and in some bacteria as well [11].…”
Section: Introductionmentioning
confidence: 99%
“…Tosun et al36 observed cartilaginous metaplasia formation after local combined HA+CS administration after Achilles tendon repair, and expressed the view that combined HA+CS administration might be useful in cartilage injuries.…”
Section: Discussionmentioning
confidence: 99%